No going back? Reversibility and why it matters for deep brain stimulation. Issue 4 (10th January 2019) - Pugh, Jonathan
Abstract : Deep brain stimulation (DBS) is frequently described as a 'reversible' medical treatment, and the reversibility of DBS is often cited as an important reason for preferring it to brain lesioning procedures as a last resort treatment modality for patients suffering from treatment-refractory conditions. Despite its widespread acceptance, the claim that DBS is reversible has recently come under attack. Critics have pointed out that data are beginning to suggest that there can be non-stimulation-dependent effects of DBS. Furthermore, we lack long-term data about other potential irreversible effects of neuromodulation. This has considerable normative implications for comparisons of DBS and brain lesioning procedures. Indeed, Devan Stahl and colleagues have recently argued that psychiatric DBS should be subject to the same legal safeguards as other forms of psychosurgery, supporting their position by forcibly criticising the claim that DBS is reversible. In this paper, I respond to these criticisms by first clarifying the descriptive and evaluative elements of the reversibility claim that supporters of DBS might invoke, and the different senses of 'reversibility' that we might employ in discussing the effects of medical procedures. I go on to suggest that it is possible to defend a nuanced version of the reversibility claim. To do so, I explain how DBS has some effects that are stimulation dependent in the short term, and argue that these effects can have significant normative implications for patient well-being and autonomy. I conclude that we should not abandon a nuanced version of the reversibility claim in the DBS debate.